PERANCANGAN APLIKASI CATALOG WISATA DI SUMATERA UTARA MENGGUNAKAN ALGORITMA RABIN-KARP - Ade Ambarwati Br Ginting; Dito Putro Utomo (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
String matching is the process of finding all occurrences of a query or called a pattern into a string or text. String matching is a string or word matching that is used in the problem to find the pattern of string characters in a sentence. String matching is a technique in determining the accuracy of a given text pattern. Attractions in North Sumatra is one of the most popular tourist destinations in North Sumatra, Lake Toba because of the beautiful scenery of many outsiders or foreigners also visit the tour. Lack of information about North Sumatra tourism objects, the authors designed a tourism catalog to help the community in finding the latest attractions in North Sumatra such as natural attractions, historical tourism, religious tourism and many more can we visit the attractions around North Sumatra. The Rabin-Karp algorithm is a hashing function to find patterns in a string. In searching a travel catalog with the Rabin-Karp algorithm, it is very suitable to use because the Rabin-Krap algorithm is used to search for a word contained in a travel search. So that the testing phase requires eclipse software in the design of making travel catalogs.Keywords: String Matching, Attraction, Tourism Catalog, Rabin-Karp Algorithm, Eclipse